2012
DOI: 10.1007/s11655-012-1060-8
|View full text |Cite
|
Sign up to set email alerts
|

The progress of the research on cardio-vascular effects and acting mechanism of polydatin

Abstract: Rhizoma Polygoni Cuspidati, a Chinese herbal drug, has actions of dispelling dampness, alleviating jaundice, clearing heat, subsiding toxin, activating blood, and removing stasis. Polydatin (PD), one of its chief active ingredients, has been proved by modern pharmacological studies to possess extensive cardiovascular pharmacological activity, showing marked effects on protecting cardio-myocyte, dilating blood vessel, antagonizing platelet aggregation, thrombosis, and atherosclerosis. The progress of the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Polydatin is an active stilbene compound which has a strong antioxidant property. 15,24 In this study, the basal level of ROS generation in cardiomyocytes was not changed by polydatin treatment alone, probably because of the basal oxidative activity was maintained successfully at a minimum in the normal physiological situation by superoxide dismutases and other endogenous scavengers of ROS. Therefore, the observations that pretreatment with polydatin completely prevented Ang II-induced superoxide generation while simultaneously blocking cardiac hypertrophy, strongly supports the hypothesis that cardiac remolding stimulated by chronic Ang II treatment is mediated mainly by oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
“…Polydatin is an active stilbene compound which has a strong antioxidant property. 15,24 In this study, the basal level of ROS generation in cardiomyocytes was not changed by polydatin treatment alone, probably because of the basal oxidative activity was maintained successfully at a minimum in the normal physiological situation by superoxide dismutases and other endogenous scavengers of ROS. Therefore, the observations that pretreatment with polydatin completely prevented Ang II-induced superoxide generation while simultaneously blocking cardiac hypertrophy, strongly supports the hypothesis that cardiac remolding stimulated by chronic Ang II treatment is mediated mainly by oxidative stress.…”
Section: Discussionmentioning
confidence: 57%
“…Evidence indicates that Res (50 μM) and PD (100 μM) produce vasorelaxation and may have therapeutic effects on hypertension and decrease coronary heart disease mortality . Oral treatment with Res results in the enhancement of agonist‐stimulated, endothelium‐dependent, and endothelium‐independent vascular relaxations in animal models of disease, such as hypertension, diabetes, and hypercholesterolemia .…”
Section: Modulation Of Calcium Signaling In the Vasculaturementioning
confidence: 99%
“…PD could be found in red wine, peanuts, hop cones, cocoa-containing products and many daily diets, 3 exhibiting a series of pharmacological activities, such as anti-oxidative, anti-inammatory, and protective effects in multiple organs (nephron-, hepatic-and cardiovascular system). [4][5][6][7][8][9][10] Furthermore, recent studies have shown that PD may act as an anti-tumor agent by inhibiting cell proliferation and inducing apoptosis in a variety of tumors. 11,12 However, current knowledge about the medicinal characteristics as well as the action mechanism of PD is still fragmented, and its system-level mechanism warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%